Experimental Study of Active Noise Control on The Motor of A UAV Aircraft Noise Vibration Centre Using A DLE Gas Engine 30 - Alfisyahrin, A; Isranuri, Ikhwansyah; Syukriyadin, S; Habiburrahman, H (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
Abstrak—The noise that occurs at the USU UAV Noise and Vibration Center ranges between 90-100 dB. The engine used is a 2-stroke engine which certainly has high noise. The engine drive motor determines the high rotation and contributes to the noise. The method used to reduce noise is ANC. ANC in this study focused only on the drive motor. The results obtained are after comparing the noise before using ANC and after using ANC. The noise reduction obtained is at a rotation of 3000 rpm with a distance of 1.25 m of 1.36 dB.